2021
DOI: 10.1017/s0003055421000356
|View full text |Cite
|
Sign up to set email alerts
|

Playing to the Gallery: Emotive Rhetoric in Parliaments

Abstract: Research has shown that emotions matter in politics, but we know less about when and why politicians use emotive rhetoric in the legislative arena. This article argues that emotive rhetoric is one of the tools politicians can use strategically to appeal to voters. Consequently, we expect that legislators are more likely to use emotive rhetoric in debates that have a large general audience. Our analysis covers two million parliamentary speeches held in the UK House of Commons and the Irish Parliament. We use a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 76 publications
(112 reference statements)
0
31
0
Order By: Relevance
“…While campaign speeches may seem the more natural forum through which politicians communicate with voters, previous work has highlighted that the single-member district electoral system in the UK provides MPs with an incentive to cultivate a personal vote (Kam 2009). Further, work on UK parliamentary speech has shown that politicians make strategic use of this forum to appeal to voters (Blumenau 2021;Osnabrügge, Hobolt and Rodon 2021). Therefore, in the UK, parliamentary speech is an appropriate forum to study my key questions of interest.…”
Section: Methodsmentioning
confidence: 99%
“…While campaign speeches may seem the more natural forum through which politicians communicate with voters, previous work has highlighted that the single-member district electoral system in the UK provides MPs with an incentive to cultivate a personal vote (Kam 2009). Further, work on UK parliamentary speech has shown that politicians make strategic use of this forum to appeal to voters (Blumenau 2021;Osnabrügge, Hobolt and Rodon 2021). Therefore, in the UK, parliamentary speech is an appropriate forum to study my key questions of interest.…”
Section: Methodsmentioning
confidence: 99%
“…I test my expectations on parliamentary QTSs from the (federal) parliaments of Belgium (Vragenuur), Croatia (Aktualno Prijepodne), and the UK (Prime Minister's Questions [PMQs]). I work with these debates because they present high gain opportunities for politicians to reach their goals due to the heavy media exposure QTSs tend to receive (Osnabrügge et al, 2021;Salmond, 2014). This makes it a perfect case of parliamentary politics to explore whether there are gender differences in attack strategies that seek to fulfil politicians' goals.…”
Section: Casesmentioning
confidence: 99%
“…In contrast to these approaches, our goal is to uncover the affective correlates of in-group favoritism and out-group derogation. To this end, we join a growing trend in the social sciences using text as data to trace difficult to measure concepts like sentiment and personality (Gennaro and Ash 2021; Osnabrugge, Hobolt, and Rodon 2021; Ramey et al 2019).…”
Section: Ethnic Identity and Judicial Bias In Comparative Perspectivementioning
confidence: 99%
“…We evaluate the mechanisms of bias through natural language processing techniques to measure affective patterns associated with favoritism or derogation (e.g., Rice and Zorn 2019). Our work joins recent work using text as data to understand the emotions, personalities, and states of mind of elites and citizens (Boussalis et al 2021;Osnabrugge, Hobolt, and Rodon 2021;Ramey et al 2019).…”
mentioning
confidence: 95%